Bumdes Bangun Mandiri Communication Strategy in Developing Villages Based on Local Wisdom in Bekiung Village - Tenerman; Irwan Syari Tanjung; Elvita Yenni (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
BUMDES Bangun Mandiri is growing rapidly by implementing various programs that synergize with the village government so that in 2022 it will produce several superior products, namely processing of local agricultural and plantation products, savings and loan units and livestock. The superior product produced is a development of village potential owned by Bekiung Village, but BUMDES Bangun Mandiri must still be able to maintain its existence in village development because it is related to improving community welfare and the village economy through communication patterns that can unite commitment with the community in achieving goals in future. Effective communication must be carried out by BUMDES Bangun Mandiri to increase public awareness which is still not optimal in developing local village products that originate from village potential so that they can compete in the industrial world. The intended local products are also one of developing the local wisdom of Bekiung Village by prioritizing village potential that can be developed in the future. The method used in this study is a qualitative method, with the method used to produce research, namely the existence of a BUMDES Bangun Mandiri communication strategy to develop villages through emphasizing local wisdom as a village economic strength to create a prosperous society.